Mixed compounds in code-switching contexts - Pierantozzi, Cristina; Cocchi, Gloria (LingBaW. Linguistics Beyond and Within, 2024)
This pilot work analyses the acceptability of mixed compound words in code-switching contexts. In particular, we will discuss mixed Italian-German and Italian-English compounds, i.e. cases of mixing among languages where the process of compounding follows different rules for what concerns the position of the head, as well as inflection issues. An Acceptability Judgment Task featuring different types of mixed compounds has been administered to two groups of participants, who are either bilingual or highly fluent in the two languages involved (Italian-German or Italian-English). Our conclusion is that it is overall possible to have mixed compounds. However, the two groups provide different judgments. For the Italian-German language pair, the possibility of mixed compounds is severely constrained, especially because of the different head-modifier parameters exhibited by the two languages and the interference of gender inflection. Though the English language patterns with German with regard to the head-modifier parameter, Italian-English participants accept a much higher number of combinations; indeed the fact that both Italian and English exhibit exocentric compounds, and that gender features do not interfere with judgments, might favour acceptability.